The role of self-control in reducing financial threat perception at The onset of COVID-19 pandemic - Octavio, Danes Quirira; Kurniawan, Dediek Tri; Fauzan, Slamet; Adristi, Fikri Irfan (JURNAL ILMU MANAJEMEN, 2024)
In this study we attempt to understand how people manage their condition during uncertainty, such as the economic crisis induced by the Covid-19 pandemic. In short,  we analyze the relationship between self-control, good financial behavior, and financial threat perception at the onset of the Covid-19 pandemic. A web-based survey was conducted to collect the sample (n = 589) in Indonesians people. This study found that self-control not only encourages good financial behavior but also reduces financial threat perception in the middle of uncertainty. However, good financial behavior cannot mediate the effect of self-control and financial threat perception. Our study provides evidence that at the onset of a financial crisis, self-control is needed to cope with acute stress that arises from sudden uncertainty. Having good financial behavior cannot fully alleviate financial threat perception. Self-control has a direct mechanism in coping with financial threats during COVID-19.Keywords: personal finance; self-control; Covid-19; pandemic; financial stress